ナンキョク ショウワキチ ナイ ノ セイブツ キゲン エアロゾル - 中嶌, 裕之; ナカシマ, ヒロユキ; Nakashima, Hiroyuki (2010)
P(論文) 南極昭和基地建物内における空気中の細菌及び糸状菌数濃度を2001年の9カ月にわたり調査した.食堂及び洗面所において,細菌数濃度は20 CFU/m^3,糸状菌数濃度は70 CFU/m^3 よりも少なかった.また,細菌及び糸状菌の日本やヨーロッパにおける平均値と比較するとそれぞれ1/50及び1/5であり,かつ季節的な変動は見られなかった.従って,昭和基地における空気中の微生物数は,室内の空調による内部環境に依存すると結論付けた. Airborne bacterial and fungal numbers in the buildings of Syowa Station in Antarctica were examined for 9 months in 2001. The number concentrations of bacteria and fungi were less than 20 and 70 CFU/m^3, respectively, in the dining room and washroom. The average number concentrations of bacteria and fungi were less than 1/50 or 1/5 of those in Japan and Europe, respectively, and remained constant regardless of season. The number concentrations of airborne microorganisms appeared to depend on drying of the indoor environment by the use of heaters. departmental bulletin paper